Tucatinib Inhibits Renal Transporters OCT2 and MATE Without Impacting Renal Function in Healthy Subjects - Topletz‐Erickson, Ariel R.; Lee, Anthony J.; Mayor, JoAl G.; Rustia, Evelyn L.; Abdulrasool, Layth I.; Wise, Amanda L.; Dailey, Ben; DeChenne, Sharon; Walker, Luke N.; Alley, Stephen C.; Endres, Christopher J. (Journal of clinical pharmacology, 2021)
Tucatinib is a potent tyrosine kinase inhibitor selective for human epidermal growth factor receptor 2 (HER2) approved by the US Food and Drug Administration for the treatment of HER2‐positive metastatic breast cancer and in development for other HER2‐positive solid tumors. Modest, reversible serum creatinine (SCr) elevations have been observed in tucatinib clinical trials. SCr is conveyed by the renal drug transporters organic cation transporter 2 (OCT2) and multidrug and toxin extrusion protein 1 (MATE1) and 2‐K (MATE2‐K) and can increase in the presence of inhibitors of these transporters. In vitro, tucatinib inhibited OCT2‐, MATE1‐, and MATE2‐K‐mediated transport of metformin, with IC50 values of 14.7, 0.340, and 0.135 µM, respectively. Tucatinib also inhibited OCT2‐ and MATE1‐mediated transport of creatinine, with IC50 values of 0.107 and 0.0855 µM, respectively. A phase 1 study with metformin administered orally in the absence and presence of tucatinib was conducted in 18 healthy subjects. Renal function was assessed by measuring glomerular filtration rate (GFR; based on iohexol plasma clearance) and endogenous markers (SCr, cystatin C‐based estimated glomerular filtration rate [eGFR]) with and without tucatinib. Metformin exposure increased (1.4‐fold) and renal clearance decreased (29.99‐17.64 L/h) with tucatinib, with no effect on metformin maximum concentration. Creatinine clearance transiently decreased 23% with tucatinib. GFR and eGFR, which are unaffected by OCT2 and/or MATE1/2‐K transport, were unchanged with tucatinib. These data demonstrate that tucatinib inhibits OCT2‐ and MATE1/2‐K‐mediated tubular secretion of creatinine, which may manifest as mild SCr elevations that are not indicative of renal impairment.